Pengaruh Edukasi Berbasis Teori Orem terhadap Selfcare Pasien DMTII di Wilayah Kerja Puskesmas Tamalanrea Makassar - Sriwahyuni Sriwahyuni; Yasir Haskas; Erna Kadrianti; Alfiah A; Hasifah Hasifah; Maryam Jamaluddin; Amriati Mutmainnah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Type II diabetes mellitus (Type II DM) is a chronic disease that requires long-term self-care skills to prevent serious complications. However, many patients have difficulty managing blood sugar levels independently due to a lack of structured and ongoing education. The Student Creativity Program (PKM) aims to improve the self-care skills of Type II DM patients through an educational approach based on the Self-Care Deficit theory from Dorothea Orem. The activity was carried out in Bonto Ramba, the working area of the Tamalanrea Makassar Health Center, involving 35 participants (33 women and 2 men). Interventions were carried out through interactive counseling, demonstrations of diabetic foot wound care, practice simulations, and the distribution of easy-to-understand educational media. Evaluation was carried out using a pre-post test to measure knowledge improvement and an observation sheet to assess the ability of self-care practice. Results showed a significant improvement in participants' self-care knowledge and skills after the intervention. In addition, family involvement in assisting patients has also increased, strengthening the sustainability of self-care behavior. Participants gave positive feedback on the method of delivering material that was contextual and relevant to daily life. The supportive-educational approach used has been proven effective in empowering patients and building awareness of the importance of self-control of health conditions. This program not only contributes to improving the quality of life of Type II DM patients, but also strengthens the role of the family as the main support in the treatment process. In conclusion, structured education based on Orem theory can be used as an intervention model that can be replicated in other areas with high prevalence of DM, as a promotive and preventive strategy in community-based management of chronic diseases.